Peluang dan Tantangan Pengembangan Souvenir Desa Wisata Berbasis Kerajinan Lokal - Gusti Ngurah Adi Wiriatama; Nyoman Dini Andiani (Masyarakat Pariwisata : Journal of Community Services in Tourism, 2021)
Tigawasa Village is one of the Old Villages or Bali Aga villages in Banjar District, Buleleng Regency, Bali which is the center of bamboo handicrafts. The local handicraft really needs development, one of the developments of the local handicrafts of Tigawasa Village, namely tourism village souvenir products. The development of local handicraft-based tourism village souvenirs is the beginning of increasing the value of local crafts in Tigawasa Village. This article describes the opportunities and challenges of developing local handicraft-based tourist village souvenirs in Tigawasa Village, which is the center of bamboo handicrafts in the Bali Aga village environment, Buleleng, Bali. The method used is a descriptive qualitative method which begins with data collection from interviews with several informants, filling out questionnaires by tourists visiting Tigawasa Village and also direct documentation to Tigawasa Village such as traditional houses and also to craftsmen in Tigawasa Village. The results show that local crafts have the opportunity to develop as souvenirs because the crafts produced are of good quality, besides that the tourism development component is also an opportunity in the development of these souvenirs such as tourists visiting Tigawasa Village will be invited to do weaving activities (something to do) with the woven results can be used as a souvenir to take home (something to buy). The results of the questionnaire also stated that 70% of tourists strongly agree with the existence of local handicraft-based tourism village souvenirs, and 30% agree and there are no opinions disagree and strongly disagree. The challenges faced related to the development of tourism village souvenirs include the limitations of existing bamboo sources so that craftsmen buy materials from outside the village so that additional capital is needed so that capital is also a challenge for Tigawasa Village crafts, lack of innovation from bamboo crafts, and lack of promotion. With the development of local handicraft-based souvenirs in Tigawasa Village can increase the selling value of local crafts, can make it a tourist attraction and as a memory for every tourist who comes to Tigawasa Tourism Village.